ANTIMICROBIAL ACTIVITIES OF SOME SAUDI ARABIAN HERBAL PLANTS - Shahat, Abdelaaty A.; Mahmoud, Elsayed A.; Al-Mishari, Abdullah A.; Alsaid, Mansour S. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Several edible plants are used in Kingdom of Saudi Arabia since early time to control microbialinfections. In the present study, twenty-four Saudi Arabian medicinal plants d according to traditionally used wereselect and investigated for the antimicrobial activitiesMaterials and Methods: This study was designed at evaluating the antimicrobial activities of the methanol extracts oftwenty-four species of sixteen plant families used in the traditional medicine by Saudi Arabian people for the treatmentof numerous ailments of the microbial and non-microbial origin against four Gram-positive, four Gram-negativebacteria and four fungi and yeast using the agar well diffusion method.Results: Of most of the plants tested were found to be active against two to eight organisms. Five plants were activeagainst eight organisms. The data appeared that extracts of Echium arabicum (SY-176), Rhantarium epapposum (SY-180), Rumex vesicarus (SY-181), Ziziphus nummularia (SY-188), Caylusea hexagyna (SY-197) and Artemisiamonosperma (SY-198) have anti-microbial activity against the most of tested bacteria, fungi and yeast. Whereas (SY-181), the extracts of Teucrium oliverianum (SY-175), Zilla spinosa (SY-187), and Rhazya stricta (SY-195) have pooraction against the tested bacteria, fungi and yeast.Conclusion: The antimicrobial activity of plant extracts against bacteria was more effective than against fungi